Rancang Bangun Sistem Pengunci Pintu Rumah Menggunakan Remote nRF24l01+ Berbasis Mikrokontroler - Suudi, Ahmad; Saputra, Anggi; Martinus, Martinus; Tanti, Novri; Lubis, Asnawi; Riszal, Akhmad (TURBO [Tulisan Riset Berbasis Online], 2023)
Home door security currently still uses a manual system using conventional door locks.  The disadvantages of conventional house door locks include that the home owner must ensure that the house key is not owned by a stranger which causes the key to be easily duplicated, as well as the number of house break-ins that cause the security of the house door to be very insecure.  To overcome the problems that occur regarding the security of the house door, the authors created a microcontroller-based door lock system using the nRF24L01+ remote as access control for opening and closing door locks. This door lock system uses 3 microcontrollers, including NodeMCU ESP8266 as a remote. Arduino Uno as the door lock system control unit, as well as the additional NodeMCU ESP8266 microcontroller as a data logging unit.  The control unit is tasked with making decisions based on commands sent by the remote via radio frequency communication from the nRF24L01+ module.  The command sent by the remote is in the form of opening and closing the door lock which comes from the input button on the remote.  It also provides additional features in the form of data logging by providing input using a limit switch attached to the door. This research got the results, namely the success of the system that is able to respond in less than one second.  The fastest response time gets a value of 0.14 seconds, then the longest response speed gets a value of 0.565 seconds, and the stable response speed gets a value of 0.188 seconds